Provocative Talk in Local American Civic Life - Samuel McCormick (European Journal of American Studies)
Many Americans are as enthusiastic about the idea of deliberative democracy as they are appalled by its actual practice, especially when it comes to local forums of civic life. In school board meetings, city council gatherings, and various public hearings across the United States, ordinary citizens have a tendency to botch, and sometimes abandon all together, the democratic ideals of reasoned debate and rational decision-making, resorting to more ordinary ways of speaking like chatter, gossip, and idle talk instead. This article explores one such example, paying special attention to the use of chatter, gossip, and idle talk for purposes of provocation, antagonism, and radical dissensus in local American civic life. Starting with a detailed qualitative case study, this essay works inductively from the specific rhetorical contours of a local public debate toward a broader philosophical perspective on the communicative practice of everyday talk, suggesting that there is always something extraordinary about ordinary civic discussion and debate.